The Right to Play - Lott, Naomi R (2020)
The right to play has been widely regarded as a forgotten right – forgotten by states implementing the Convention on the Rights of the Child (Convention), ignored by the United Nations Committee on the Rights of the Child (Committee) in monitoring and providing guidance on the Convention, and neglected by human rights academics. Wide-ranging extensive research shows the vital importance of play in supporting the holistic development of the child. In light of this, the thesis scrutinises the right to play – the raison d’être of the right, the challenges faced in realising the right, and the obligations pertaining to the right. It does so in order to investigate the causes of the right’s ‘forgotten’ status and to offer recommendations for remedying such. The thesis provides a vital investigation into and critique of the situation facing the realisation of the right to play, providing a necessary and overdue contribution to the child rights field. The thesis examines the right to play and its implementation through analysing extensive multidisciplinary research on the value of play for children, both intrinsically and instrumentally, and the wide-ranging challenges surrounding children’s play, providing in-depth discussion on implications for the realisation of the right to play. The thesis considers the legal background of the right to play, from the drafting process of the Declaration of the Rights of the Child and Convention to the work of the Committee in its General Comments, Concluding Observations and Days of General Discussion. The author then investigates the obligations pertaining to the right to play before triangulating the research in the thesis through a multiple case study of the United Kingdom and Tanzania. The thesis highlights elements of best practice, challenges and weaknesses in realising the right to play, and recommendations for continued and improved realisation of the right to play.